(untitled) (Iter, 2022)
In the Greek world of the 5th century BC, Nomos and associated concepts suffer the confrontation of Physis, which can represent a stronger law. In the work of Thucydides, appealing to the nature seems normal in the field of relations between States. Although there are actors in this field that prefer to invoke the nomos in the sense of a moral law or customary use, it may be no more than fine words that have no force in the reality (the erga). In the internal order of a State, traditional nomos retains its validity, except when a revolutionary crisis trasvalore its meaning and simply force prevails. And in an order that is located between the inner and the outer, the political chief can not act simply according to the moral values that he can appreciate; because he acts in a field in which governs the law of nature, he has to meet requirements higher than the private virtue. Nomos and Physis are thus intertwined in the Thucydidean work, at times in tragic way.